English as a foreign language learning in Colombia: an overview from seventh-grade students perspectives. (2024)
This case study aimed to analyze how the students' beliefs are taking part in the learning process of English as a foreign language in their context and the implications of those during the acquisition of it through the recognition of the limitations encountered by them in the foreign language classroom by using a qualitative method. Hence, this investigation focused on the perceptions of three students selected from a sample of ten, based on their ethnicity, socioeconomic strata, gender, and age to respond to an interview that yielded three major findings mostly related to the instrumental use of the language, the students' mentality and willingness to learn it as well as the most challenging aspects of their learning process. The data collected showed that the main belief of students revolved around the perception of English as a language capable of improving their life prospects through obtaining benefits in future job opportunities or professional development, along with the connection of cognitive process with their willingness to learn the language and the challenges related with mastering grammar rules and structures which are closely linked with the explicit grammar instruction method used in the English lessons. Thus, it is concluded that understanding students' motivational factors, beliefs, and perceptions is fundamental to constructing significant experiences in the foreign language classroom while analyzing the teaching strategy used and its effects on the learning processes to re-designing or reconsidering the educational practices to attend to students' needs and perceptions. Keywords: Students’ beliefs, language learning perceptions, contextualized learning, English as a foreign language, language learning.